Food Security As And National Security: A Management Approach (Journal of Politics and International Studies, 2023)
National security refers to ensuring the safety of the citizens and the protection of the state. It is imperative to understand that national security cannot be achieved unless the basic need of food security is met. Prioritizing food security can make the world a safer place, even for sovereign nations. Unfortunately, most of the time this fundamental aspect of national security is overlooked. The government must prioritize food security because it has an impact on the safety and security of Pakistan. Inadequate access to food has resulted in protests, civil unrest, and even terrorist attacks. Poor economic growth can also destabilize social and political orders, posing a significant threat to national security. This research aims to analyze the critical role of food security in national security in Pakistan, using qualitative analysis and data from the Food and Agricultural Organization (FAO). The findings indicate that if population growth continues at the current rate, Pakistan will become food insecure in 2030. Thus, prioritizing food security could significantly contribute to enhancing the security condition in Pakistan.